A Simplified Method for Establishing Safe Available Evacuation Time Based on a Descending Smoke Layer - Pokorny, Jiri; Mozer, Vladimir; Malerova, Lenka; Dlouha, Dagmar; Wilkinson, Peter (Communications - Scientific letters of the University of Zilina, 2018)
Keeping the smoke layer at a safe height is one of the most important tenability criteria in assessment of evacuation from buildings. The basis of this approach is an accurate approximation of the fire and smoke plume, which is formed above the fire source. The major variables affecting smoke filling are the fire growth rate and enclosure geometry, i.e. the floor area and height. This paper deals with the implementation of a new method for establishing safe available evacuation time based on the fundamental principles of smoke generation and flow into the national fire safety design standards in the Czech and Slovak Republic. Some of these calculation methods have also been included in fire safety engineering ISO standards. The devised method is based on the t-squared fire growth model and correlations for smoke production and air entrainment into the rising plume of smoke. Subsequently, the proposed method is validated against a wide range of benchmark scenarios in the two-zone fire model CFAST. The paper compares the differences, comments on their causes and evaluates the applicability of the new method in both countries. The proposed method is not only compatible with the national fire safety design standards, but also allows for a more precise assessment of life safety without the need for overly complicated calculations.